2018
DOI: 10.1002/cphc.201701068
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Differences in Spin Couplings for Various Self‐Paired Dimers of Ring‐Expansion‐Radicalized Uracil: A Basis for the Design of Magnetically Anisotropic Assemblies

Abstract: The spin-coupling properties of a series of radicalized uracil (rU) dimer diradicals with different H-bonding modes is examined. Each rU has four double H-bonding sites [the amide units: two at the Watson-Crick face (upper site WC and lower site WC ), a Hoogsteen site (HO), and a minor-groove site (MI)], and ten homogeneous dimers (rU-rU) can self-pair with well-defined diradical characters and comparable stability to the native U dimers. More interestingly, all these dimers exhibit distinctly different spin-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The site arrangement of radical modification on the left and right sides of the base pair will result in many different combinations. In previous studies, ,,, it is found that the intermolecular magnetic exchange coupling constants produced by this form of combination are generally very small. The same pattern has been found in the present study, in which seven groups with relatively large magnetic exchange coupling constants were selected.…”
Section: Resultsmentioning
confidence: 99%
“…The site arrangement of radical modification on the left and right sides of the base pair will result in many different combinations. In previous studies, ,,, it is found that the intermolecular magnetic exchange coupling constants produced by this form of combination are generally very small. The same pattern has been found in the present study, in which seven groups with relatively large magnetic exchange coupling constants were selected.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that all of the intermolecular nitroxide diradical base pairs show weak magnetic spin couplings, which is in good agreement with the results obtained in our previous work. 39,41,42 Diradical spin coupling between two nucleobases does not follow the spin-alternating rule, and thus we can only determine the magnetic coupling characteristics through the SOMOs and spin density distributions. Because the two nitroxide radicals are connected by weak interaction of hydrogen bonds, their magnetic spin coupling characteristics are not remarkable, and their spin coupling constants |J| are between 0 and 3 cm −1 .…”
Section: Nomentioning
confidence: 99%
“…First, the development of new assembly structures include the incorporation of other nanoparticles, such as metal modification (M-DNA), hybridization, and so forth. Second, DNA bases are modified by ring expansion or metal modification, such as changing their magnetic, electrical, and optical properties. In the latter case, our team has designed a series of basic monomer and base pair combinations and discussed in more detail and extensively. We have successfully introduced radicals into DNA bases, giving them new magnetic properties, while also greatly improving their electronic properties, redox activity, and the like. , However, slightly less than that, while giving radical properties, the size of radical bases is also widened, which to some extent weakens the magnetic coupling between the radicals. Therefore, the magnetic coupling properties of such novel DNA diradicals are not very prominent.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the self-complementary dimers of cyclopentadiene-ring-expanded uracil have been developed to provide an application foundation for the design and assembly of anisotropically bio-inspired magnetic membranes. 15 Another important subject in this field is the tunability of spin states or magnetic properties, which has a broad application in molecular electronics and data storage devices. To data, the pH-, temperature-, and photo-induced methods are found to be responsible for the magnetic reversal phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bu and Zhao revealed that the DNA nucleobases are functionalized by nitroxide diradicals, which are promising for building blocks of the biomimetic magnetic nanodevices or nanomaterials. Recently, the self-complementary dimers of cyclopentadiene-ring-expanded uracil have been developed to provide an application foundation for the design and assembly of anisotropically bio-inspired magnetic membranes …”
Section: Introductionmentioning
confidence: 99%